NAD-Linked Metabolism and Intervention in Short Telomere Syndromes and Murine Models of Telomere Dysfunction - Stock, Amanda J; Liu, Yie (Frontiers in Aging, 2021)
Telomeres are specialized nucleoprotein structures that form protective caps at the ends of chromosomes. Short telomeres are a hallmark of aging and a principal defining feature of short telomere syndromes, including dyskeratosis congenita (DC). Emerging evidence suggests a crucial role for critically short telomere-induced DNA damage signaling and mitochondrial dysfunction in cellular dysfunction in DC. A prominent factor linking nuclear DNA damage and mitochondrial homeostasis is the nicotinamide adenine dinucleotide (NAD) metabolite. Recent studies have demonstrated that patients with DC and murine models with critically short telomeres exhibit lower NAD levels, and an imbalance in the NAD metabolome, including elevated CD38 NADase and reduced poly(ADP-ribose) polymerase and SIRT1 activities. CD38 inhibition and/or supplementation with NAD precursors reequilibrate imbalanced NAD metabolism and alleviate mitochondrial impairment, telomere DNA damage, telomere dysfunction-induced DNA damage signaling, and cellular growth retardation in primary fibroblasts derived from DC patients. Boosting NAD levels also ameliorate chemical-induced liver fibrosis in murine models of telomere dysfunction. These findings underscore the relevance of NAD dysregulation to telomeropathies and demonstrate how NAD interventions may prove to be effective in combating cellular and organismal defects that occur in short telomere syndromes.